1986
DOI: 10.3386/w1862
|View full text |Cite
|
Sign up to set email alerts
|

New Results on the Effects of Tax Policy on the International Location of Investment

Abstract: Foreign direct investment (FDI) in the United States and U.S. direct investment abroad (DIA) are important economic phenomena as well as a source of political controversy. In 1980, FDI reached $17 billion, about 22% as large as net domestic fixed investment. Correspondingly, DIA reached $19 billion, about 25% as large as net domestic investment in plant and equipment. Since 1980, substantial FDI has continued, whereas DIA has fallen precipitously. Further, the sources of finance for FDI and the uses of earning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
5

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 14 publications
4
59
0
5
Order By: Relevance
“…The study found a strong and positive impact of the tax rate on FDI. Similar results were found by Boskin and Gale (1987), Young (1988), Murthy (1989), Grubert and Mutti (1991), Hines and Rice (1994), Gorter and Parikh (2000), and Benassy-Quere et al (2001); all find evidence to show a statistically significant impact of tax on FDI. Any form of FDI involves the process of converting currency from the home country to that of the host nation.…”
Section: Methodssupporting
confidence: 76%
“…The study found a strong and positive impact of the tax rate on FDI. Similar results were found by Boskin and Gale (1987), Young (1988), Murthy (1989), Grubert and Mutti (1991), Hines and Rice (1994), Gorter and Parikh (2000), and Benassy-Quere et al (2001); all find evidence to show a statistically significant impact of tax on FDI. Any form of FDI involves the process of converting currency from the home country to that of the host nation.…”
Section: Methodssupporting
confidence: 76%
“…možnost dosáhnout na daňové úlevy (viz např. Hartman, 1984;Boskin, Gale, 1986;Slemrod, 1990;Swenson, 1994;Lanaspa, Pueyo, Sanz, 2005;Mutti, Grubert, 2004;Simmons, 2003;Buettner, Ruf, 2007;Buettner, Wamser, 2006;Keuschnigg, 2009;Mooij, Ederveen, 2003).…”
Section: Zdanění V Neoklasickém Růstovém Modeluunclassified
“…Boskin and Gale (1987) extend the Hartman analysis by using a longer time series from 1956 -1984 and alternative data for the rate of return. They also experiment with a linear instead of a log specification.…”
Section: Time Series Fdimentioning
confidence: 99%